At Home Photography-Based Method for Measuring Wrist Range of Motion - Trehan, Samir K.; Rancy, Schneider K.; Johnsen, Parker H.; Hillstrom, Howard J.; Lee, Steve K.; Wolfe, Scott W. (Journal of Wrist Surgery, 2017)
Purpose To determine the reliability of wrist range of motion (WROM) measurements based on digital photographs taken by patients at home compared with traditional measurements done in the office with a goniometer.Methods Sixty-nine postoperative patients were enrolled in this study at least 3 months postoperatively. Active and passive wrist flexion/extension and radial/ulnar deviation were recorded by one of the two attending surgeons with a 1-degree resolution goniometer at the last postoperative office visit. Patients were provided an illustrated instruction sheet detailing how to take digital photographic images at home in six wrist positions (active and passive flexion/extension, and radial/ulnar deviation). Wrist position was measured from digital images by both the attending surgeons in a randomized, blinded fashion on two separate occasions greater than 2 weeks apart using the same goniometer. Reliability analysis was performed using the intraclass correlation coefficient to assess agreement between clinical and photography-based goniometry, as well as intra- and interobserver agreement.Results Out of 69 enrolled patients, 30 (43%) patients sent digital images. Of the 180 digital photographs, only 9 (5%) were missing or deemed inadequate for WROM measurements. Agreement between clinical and photography-based measurements was “almost perfect” for passive wrist flexion/extension and “substantial” for active wrist flexion/extension and radial/ulnar deviation. Inter- and intraobserver agreement for the attending surgeons was “almost perfect” for all measurements.Discussion This study validates a photography-based goniometry protocol allowing accurate and reliable WROM measurements without direct physician contact. Passive WROM was more accurately measured from photographs than active WROM. This study builds on previous photography-based goniometry literature by validating a protocol in which patients or their families take and submit their own photographs.Clinical Relevance Patient-performed photography-based goniometry represents an alternative to traditional clinical goniometry that could enable longer-term follow-up, overcome travel-related impediments to office visits, improve convenience, and reduce costs for patients.
Keywords: wrist goniometry; wrist range of motion; digital images; distance learning; remote access